Assyrian and Babylonian Scholarly Text Catalogues. Medicine, Magic and Divination - Steinert, Ulrike (Die babylonisch-assyrische Medizin in Texten und Untersuchungen, 2018)
The reconstruction of ancient Mesopotamian medical, ritual and omen compendia and their complex history is still characterised by many difficulties, debates and gaps due to fragmentary or unpublished evidence. This book offers the first complete edition of the Assur Medical Catalogue, an 8th or 7th century BCE list of therapeutic texts, which forms a core witness for the serialisation of medical compendia in the 1st millennium BCE. The volume presents detailed analyses of this and several other related catalogues of omen series and rituals, constituting the corpora of divination and healing disciplines. The contributions discuss links between catalogues and textual sources, providing new insights into the development of compendia between serialization, standardization and diversity of local traditions. Though its a novel corpus-based approach, this volume revolutionizes the current understanding of Mesopotamian medical texts and the healing disciplines of conjurer and physician. The research presented here allows one to identify core text corpora for these disciplines, as well as areas of exchange and borrowings between them.